Intermittent and continuous imatinib in a human GIST xenograft model carrying KIT exon 17 resistance mutation D816H. (May 2013) - Revheim, Mona-Elisabeth; Kristian, Alexandr; Malinen, Eirik; Bruland, Øyvind Sverre; Berner, Jeanne-Marie; Holm, Ruth; Joensuu, Heikki; Seierstad, Therese
Abstract Background. Acquired resistance to imatinib is frequently caused by secondary KIT mutations. We have investigated the effects of imatinib in mice with human gastrointestinal stromal tumour (GIST) xenograft which harbours a primary exon 11 deletion mutation and a secondary imatinib resistance mutation D816H in exon 17. Such mutations are commonly present in imatinib-resistant GIST in humans. Material and methods. The mice were randomly allocated to receive imatinib either continuously or intermittently. Dynamic 18F-FDG PET was performed and blood volume fraction (vB), rate transfer constants (k1, k2, k3) and metabolic rate of 18F-FDG (MRFDG) were computed using a three-compartment model. Tumours were evaluated for the mitotic rate and the expression of HIF-1α, caspase-3 and glucose transporters (GLUTs). Results. Both intermittent and continuous imatinib delayed tumour growth significantly compared to controls, significantly in favour of the latter. k1 (representing perfusion, vascular permeability and binding of 18F-FDG to the GLUTs) was significantly higher in the intermittent group compared to the continuous group, as was tumour GLUT-3 expression. k3 (representing internalisation of 18F-FDG to the cells) and MRFDG were significantly lower. Conclusion. Imatinib delays GIST xenograft growth despite the presence of the D816H resistance mutation. The schedule of imatinib administration may influence tumour glucose uptake rate and metabolic rate.